MEMBANGUN PENCITRAAN PUBLIK SEKOLAH ISLAM MELALUI MEDIA SOSIAL DAN TEKNOLOGI DIGITAL - Nanik Purwiningsih; Rustam Ibrahim (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze innovative collaboration management strategies amid the development of digital technology and their impact on organizational effectiveness. The study employed a qualitative approach using a library research method by reviewing various scientific literature, books, journals, theses, dissertations, and relevant regulations published within the last ten years. Data collection techniques were conducted through documentation and content analysis to obtain an in-depth understanding of digital-based collaboration management transformation. The findings revealed that the development of digital technology has transformed organizational collaboration patterns from conventional systems into technology-based collaborative systems. The innovative strategies implemented include the utilization of digital communication platforms, data-based management information systems, strengthening human resource digital literacy, and developing organizational cultures adaptive to technological changes. The implementation of these strategies improves communication effectiveness, operational efficiency, organizational transparency, and the expansion of collaboration networks. However, several challenges remain, such as data security, unequal access to technology, and resistance to change. Therefore, organizations need to strengthen digital infrastructure and improve human resource competencies to optimally face the challenges of digital transformation.